2014
DOI: 10.3233/nre-141077
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care-testing of standing posture with Wii balance board and microsoft kinect during transcranial direct current stimulation: A feasibility study

Abstract: BACKGROUND: Non-invasive brain stimulation (NIBS) is a promising tool for facilitating motor function. NIBS therapy in conjunction with training using postural feedback may facilitate physical rehabilitation following posture disorders (e.g., Pusher Syndrome). OBJECTIVES:The objectives of this study were, 1) to develop a low-cost point-of-care-testing (POCT) system for standing posture, 2) to investigate the effects of anodal tDCS on functional reach tasks using the POCT system. METHODS: Ten community-dwelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 0 publications
1
28
1
4
Order By: Relevance
“…Similarly, Craig and Doumas (7) found that M1 stimulation had positive effects on the sway amplitude of older adults. In line with studies on older adults, it was reported that M1 facilitation could improve balance in young adults (7,30,31) and patients with Parkinson's disease (32), chronic low back pain (33), and stroke (34).…”
Section: Effect Of M1 Tdcs On Balancesupporting
confidence: 53%
“…Similarly, Craig and Doumas (7) found that M1 stimulation had positive effects on the sway amplitude of older adults. In line with studies on older adults, it was reported that M1 facilitation could improve balance in young adults (7,30,31) and patients with Parkinson's disease (32), chronic low back pain (33), and stroke (34).…”
Section: Effect Of M1 Tdcs On Balancesupporting
confidence: 53%
“…58 found good test-retest and between-device intra-class correlation coefficient (>0.66). Moreover, the use of the Wii Balance Board as a posture measure tool was validated in young people 31,32 , elderly 59 , persons with Parkinson's disease 60 , visual impairment 61 , and reconstructed anterior cruciate ligament 62 . A software (Polyenco, France) was specifically developed to connect the Wii Balance Board to the computer in order to display the CoP position in a form of a cross on the screen, and randomly picture the targets to validate (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…tDCS has a beneficial safety profile (Fregni et al, 2015) and has been shown to allow promotion of long-lasting enhancements of learning and neuroplasticity in health and disease (Cohen Kadosh et al, 2010, Meinzer et al, 2016, Meinzer et al, 2014, Reis et al, 2009. Moreover, a number of previous studies have demonstrated that tDCS administered to cortical sites, like the primary motor or prefrontal cortex, can enhance postural control in healthy individuals (Dutta et al, 2014, Zhou et al, 2014 and in patients with cerebral palsy, Parkinson's disease and stroke (Fregni et al, 2006, Grecco et al, 2017, Kaski et al, 2014, Saeys et al, 2015 However, while previous studies have demonstrated that cerebellar tDCS (ctDCS) can improve motor learning in healthy individuals (e.g., Block and Celnik, 2013, Galea et al, 2009, Hardwick and Celnik, 2014, potential beneficial effects on postural control have not yet been investigated. Such an approach would be of particular interest as an adjunct treatment approach in patients with cerebral lesions where clinicians are interested to facilitate activity in spared cortical regions that rely on cerebellar inputs (Grimaldi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%